PROFITABILITAS, SALES GROWTH, LEVERAGE, UKURAN PERUSAHAAN DAN PENGHINDARAN PAJAK: BUKTI DARI PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI - Mukhammad Fauzi; Dr. Deden Tarmidi, SE., M.Ak., BKP.; Yudhi Herliansyah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
ABSTRACT The case of tax avoidance that occurs in Indonesia can show a form of weakness that occurs in the law, many companies do tax avoidance that causes losses to the state. This study aims to analyze and obtain empirical evidence on the effect of profitability, sales growth, leverage and company size on tax avoidance. The independent variables used in this study are profitability, sales growth, leverage and company size. The dependent variable used in this study is tax avoidance. The sample in this study consisted of 8 consumer goods industry sector companies listed on the Indonesia Stock Exchange (IDX) in 2014-2021. With non-probability sampling techniques with purposive sampling type. The data used in this study is secondary obtained from the official website of the Indonesia Stock Exchange and the official website of each company. The results of this study found the effect of profitability and leverage on tax avoidance, while sales growth and firm size had no significant effect. These results can be input for the tax authorities in analyzing taxpayers' tax avoidance from information on profitability and leverage.